2017
DOI: 10.1140/epjb/e2017-70722-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantum subdiffusion with two- and three-body interactions

Abstract: We study the dynamics of a few-quantum-particle cloud in the presence of two-and three-body interactions in weakly disordered one-dimensional lattices. The interaction is dramatically enhancing the Anderson localization length ξ1 of noninteracting particles. We launch compact wave packets and show that few-body interactions lead to transient subdiffusion of wave packets, m2 ∼ t α , α < 1, on length scales beyond ξ1. The subdiffusion exponent is independent of the number of particles. Two-body interactions yiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This procedure resembles a one elaborated previously for the analysis of two interacting quantum particles (e.g. bosons) moving on a one-dimensional periodic lattice [37,38].…”
Section: Energy Spectrum Of Two Interacting Mfs: Tight-binding Model ...mentioning
confidence: 99%
“…This procedure resembles a one elaborated previously for the analysis of two interacting quantum particles (e.g. bosons) moving on a one-dimensional periodic lattice [37,38].…”
Section: Energy Spectrum Of Two Interacting Mfs: Tight-binding Model ...mentioning
confidence: 99%
“…To assess TIW localization length scales we will project p ij in three different ways onto a one-dimensional coordinate space and compute the standard deviation of a probability distribution vector {v i } (see e.g. [21,22])…”
Section: B Tiwmentioning
confidence: 99%
“…The challenging study of the interplay of interaction and disorder leads to a number of unexpected results for the localization properties of many particles eigenstates. The seemingly simplest case of two interacting particles (TIP) in one space dimension was analyzed in an impressive set of publications [10][11][12][13][14][15][16][17][18][19][20][21][22]. For uncorrelated disorder the TIP localization length ξ 2 is assumed to be finite, with the main questions addressing the way ξ 2 scales with ξ 1 in the limit of weak disorder [10][11][12][13][14][15][16][17][18][19][20], and the nature of the observed sub-diffusive wave packet spreading on length scales ξ 1 L ξ 2 [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…While some recent work has shown that localiza-tion can persist in the presence of three-body interactions [60,61], most studies of thermalization to date focus on two-body interactions. Three-and four-body interactions have been observed in both cesium and rubidium [62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%